(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdQgfs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdQgf hGdfXQ ajg jSJOYj aUhdG GdChd aj GdQgf, Cbhd GYde Cf GdQgf SGFZ HGdfU hGdGLJeGY, bGd Gddg(B: (3Ke QgGf ebHhdIs
(3BNQgG (B:s
(3BNQgG(B: (3Cbhd UnqQM ZjQ hGMO ef CUMGHfG HYOe hLhH GJNGP Pdc, bdJ(B: (3Hd gh GdPj JbJVjg bGYOI GdeOYj hGdefcQ (B.. (3YfgG aj GdebGe adGMX hJCed(B. (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis